Two terminal devices for the CISS effect analytical and modeling - Sanmartin Castillo, Miguel Angel (2022)
Outstanding experimental results in chiral molecules show preferential spin transport depending on the chirality in two terminal measurements (Chirally induced Spin Selectivity or CISS). Theorists have proposed that this spin active devices are driven by the Spin-Orbit interaction (SOI). Nevertheless, such an interaction in terminal devices is forbidden to spin filter due to the symmetry imposed by Onsager relations in the linear regime. We will show that experiments do no correspond to the theoretical two-terminal-setup so that the two terminal “theorem” does not apply. In this work we propose to study a model of a Time reversal invariant spin-orbit coupled molecule such as DNA and Oligopeptides that are also spatially chiral and thus lack an inversion center. We will begin by deriving the main elements, from a macroscopic transmission matrix approach, the behavior of a two-terminal device, including the spin-sensitive interface. While the theoretical treatment predicts zero two-terminal magnetoresistance (MR) sensitive to spin, we find these results from a misinterpretation of the experimental setups which do indeed show spin-sensitive MR.